Treatment Outcomes of Dipeptidyl Peptidase-4 Inhibitors and Sodium-Glucose Co-Transporter-2 Inhibitors in Diabetes Mellitus with Poor Glycemic Control - Kabir, SK Md Humayun; Islam, Md Khairul; Sultana , Masuma; Naznin, Afsana; Akter , Nargis; Alam, Md Nur; Das , Adhir Kumar (Journal of Medicine, 2024)
Background: Diabetes, a progressive disease necessitating multifaceted pharmacological interventions for glycemic control, commonly employs Dipeptidyl Peptidase-4 inhibitors (DPP-4i) and Sodium-Glucose Co-Transporter-2 inhibitors (SGLT-2i). The ongoing challenge lies in determining the superior option for safety and efficacy. Objective: This study aims to describe the treatment outcomes of DPP-4 inhibitors (DPP-4i) and Sodium- Glucose Co-Transporter-2 inhibitors (SGLT-2i) in individuals with diabetes mellitus (DM) receiving metformin with poor glycemic control. Methods: This prospective study was conducted at the Endocrinology Outpatient Department of Dhaka Medical College Hospital, Dhaka, and included 90 individuals with diabetes mellitus who met the selection criteria. Divided into two groups, Group I (n=45) received DPP-4 inhibitors plus metformin, and Group II (n=45) received SGLT2 inhibitors plus metformin. Baseline data, including HbA1c, fasting blood glucose (FBG), blood glucose 2 hours after breakfast, weight, lipid profile, and serum creatinine, were recorded at the first visit and 12 weeks. Safety was assessed based on adverse drug effects. Results: After 12 weeks, both groups exhibited significant reductions in HbA1c, FBG, and postprandial blood glucose levels. However, the SGLT-2i group demonstrated significant improvements in HbA1c (P<0.012), fasting plasma glucose (P<0.003), and postprandial glucose levels (P<0.001), along with a reduction in body weight (P<0.042). Hypoglycemia rates were low and balanced between groups. Notably, SGLT-2i usage correlated with an increased incidence of urinary tract infections (13.33% vs. 6.66% in DPP-4i) and exclusive genital infections (11.11%, P<0.022). Conclusion: Diabetic patients receiving SGLT-2 inhibitors had better glycemic control and body weight improvements in comparison to DPP-4 inhibitors. However, SGLT-2 inhibitors encountered more genital infections than DPP-4 inhibitors. J MEDICINE 2024; 25: 107-114